A method for preparing aramid and nylon skeleton material for aviation tire crown belt strip

CN119162710BActive Publication Date: 2026-10-30QINGDAO TIPONT CORD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411219195.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2026-10-30
Estimated Expiration
2044-09-02

AI Technical Summary

Technical Problem

例如,芳纶1500D/2与N661890D/1的组合,虽然其已经展现出了较好的物理与化学性能,但仍面临如密度较高导致轮胎增重,进而影响飞机性能等问题

Benefits of technology

[0022]本发明采用了低线密度的芳纶+尼龙组成复合骨架材料,这一选择不仅基于其优异的机械性能与轻质特性,还充分考虑了材料成本效益的最大化。通过精密设计的多股捻线工艺,将芳纶+尼龙纤维多次加捻缠绕,再通过三种浸胶液浸渍处理,这一过程显著增强了纤维间的相互抱紧力,从而在宏观层面上实现了材料整体强度的显著提升。这种增强机制不仅优化了材料的力学性能,如拉伸强度、耐磨性和抗疲劳性,还使得最终产品在保持高强度的同时,实现了重量的显著减轻,满足航空轮胎对轻量化的要求;同时还进一步降低了生产和使用过程中的能耗与成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the field of aviation tire manufacturing, in particular to a preparation method of aramid and nylon framework material for an aviation tire crown belt strip.S1. initial twisting; one 1100 dtex aramid original wire is twisted on a ring twister, the twisting direction is Z direction, the twist is 240-300 twists per meter, and the twisting is three times; one 940 dtex nylon original wire is twisted on the ring twister, the twisting direction is Z direction, the twist is 160-200 twists per meter, and the twisting is twice; S2. plying and twisting; the twisted three aramid wire strands and two nylon wire strands are plied, the plied yarn is twisted in the reverse S direction, the twist is 240-300 twists per meter, and the obtained blended yarn rope is obtained; S3. gum dipping; S4. preparing a finished yarn rope; the blended yarn rope is placed in a drafting machine and drafted under the condition of 210-235 DEG C, and the finished yarn rope is obtained. The nylon with low linear density is selected, the holding force is increased through the multi-strand twisting process, the strength is improved, the cost is reduced, and the physical and chemical indexes are improved compared with the previous patent products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aircraft tire manufacturing, and more specifically to a method for preparing aramid and nylon skeleton materials for aircraft tire crown strips. Background Technology

[0002] The aviation tire industry has historically been known for its robustness, with a relatively conservative radial design and a slow pace of adopting new technologies and materials. However, with the booming development of the aerospace industry, the performance of aviation tires has seen a significant leap forward. These tires not only face extreme challenges such as heavy loads, high-speed operation, extreme deformation, and high-pressure inflation, but also need to exhibit excellent impact resistance, puncture resistance, and high-temperature resistance, while withstanding the enormous centrifugal force during takeoff and the violent impact at landing. In addition, lightweight design is also an indispensable requirement for aviation tires; overall, the performance requirements are extremely stringent.

[0003] The construction of aircraft tires is similar to that of other tires, with the core consisting of rubber and a reinforcing material, in which the reinforcing material plays a crucial role. As the component that bears the main stress, the reinforcing material must possess high strength, low mass density, low moisture absorption, excellent impact resistance and high temperature resistance, fatigue resistance, and ideal constant load and elongation at break to meet the stringent requirements of aircraft tires in terms of high pressure, high speed, large deformation, and lightweight design.

[0004] Historically, cotton cord was initially used as the skeleton material for aircraft tires. However, due to its limited strength, this resulted in tires with many layers, a thick and heavy structure, and poor fatigue resistance. It was gradually replaced by superior synthetic fibers such as nylon and polyvinyl chloride. Nylon is known for its high strength, low density, good elasticity, low moisture absorption, high impact strength, and flexural strength; while nylon exhibits excellent wear resistance, fatigue resistance, chemical stability, and dimensional stability. However, using nylon or polyvinyl chloride cord alone also has limitations, such as insufficient thermal stability, susceptibility to creep, significant tire expansion after long-term use, and negative impacts on overall tire performance, lifespan, and shock resistance.

[0005] Therefore, the current mainstream trend is to use composite skeleton materials, especially the combination of aramid and nylon / nylon to create composite cords. This design achieves complementary advantages by carefully adjusting the twist count, twist direction, denier, and number of strands of aramid and nylon / nylon. For example, the combination of aramid 1500D / 2 and N661890D / 1, although it has shown good physical and chemical properties, still faces problems such as the higher density leading to increased tire weight, which in turn affects aircraft performance. Summary of the Invention

[0006] This invention provides a method for preparing aramid and nylon skeleton materials for aircraft tire crown strips. The purpose is to reduce the density of the composite skeleton material by using a new process, while ensuring the improvement of the physical and chemical properties of the aramid and nylon skeleton materials, so as to reduce the weight of the tire and meet the requirements of lightweight aircraft tires.

[0007] To achieve the above objectives, the technical solution of the present invention is as follows:

[0008] This invention provides a method for preparing aramid and nylon skeleton materials for aircraft tire crown strips, comprising the following steps:

[0009] S1. Initial twisting: On a ring twisting machine, a 1100 dtex aramid filament is twisted in the Z direction with a twist of 240-300 twists / meter, for a total of three twists; On a ring twisting machine, a 940 dtex nylon filament is twisted in the Z direction with a twist of 160-200 twists / meter, for a total of two twists.

[0010] S2. Plying and twisting: Ply the three aramid yarn strands and two nylon yarn strands together, and twist the plied yarn in the opposite S direction with a twist of 240-300 twists / meter to obtain a blended yarn rope.

[0011] S3. Impregnation: The blended yarn is immersed in a first-bath impregnation solution at a temperature of 25-30°C for 2-6 seconds. The first-bath impregnation solution is an aqueous adhesive. The yarn is then removed and dried at 100-120°C for 1.2-1.5 minutes. The dried yarn is then immersed in a second-bath impregnation solution at a temperature of 25-30°C. The second-bath impregnation solution is a CBI-50 aqueous solution. The yarn is then removed and activated at 180-215°C for 1.2-1.5 minutes. After activation, the yarn is immersed in a third-bath impregnation solution at a temperature of 20-30°C for 2-6 seconds. The third-bath impregnation solution is an RFL adhesive. Finally, the yarn is removed and heat-set at 210-235°C for 1.2-1.5 minutes.

[0012] S4. To prepare the finished cord, the heat-set blended cord is placed in a drawing machine and drawn at 210-235℃. The drawing tension of the drawing machine is 280-320g / cord, and the machine speed is 4-6 meters / minute, thus obtaining the finished cord.

[0013] Furthermore, the ratio of the length of the aramid filament to the length of the nylon filament is 1.08:1.

[0014] Furthermore, the preparation method of the one-bath impregnation solution is as follows: at room temperature of 20-25°C, first add 0.1g of wetting agent OT with a solid content of 10%-15% to 96g of softened water and stir evenly, then add 2.9g of EX-313 epoxy resin, stir evenly, and let stand for eight hours.

[0015] Furthermore, the preparation method of the two-bath impregnation solution is as follows: at room temperature of 20-25°C, pour 10g of CBI-50 with a solid content of 50% into 90g of softened water, stir evenly, and it can be used directly.

[0016] Furthermore, the preparation method of the three-bath impregnation solution includes the following steps:

[0017] 1) At room temperature of 20-25℃, add 2Kg of resorcinol-formaldehyde resin with a solid content of 75% to 23Kg of softened water, stir evenly, then slowly add 3Kg of ammonia water with a concentration of 25% while stirring, until all is added and stirred evenly. After standing for 8 hours, solution A is obtained.

[0018] 2) At room temperature of 20-25℃, 35Kg of butyl rubber latex with a solid content of 40% was mixed with 15Kg of softened water and 5KG of natural rubber latex with a solid content of 60%, and stirred evenly to obtain solution B.

[0019] 3) At room temperature of 20-25℃, 1 kg of formaldehyde is mixed with 11 kg of softened water to obtain solution C;

[0020] 4) At room temperature of 20-25℃, add solution A to solution B and stir well. Then slowly add solution C last, stirring constantly until all the solution is added and stirred well. After standing for 24 hours, the RFL adhesive solution is obtained.

[0021] The beneficial effects achieved by this invention are as follows:

[0022] This invention employs a composite skeleton material composed of low-linear-density aramid and nylon. This choice is based not only on their excellent mechanical properties and lightweight characteristics but also on maximizing material cost-effectiveness. Through a precisely designed multi-strand twisting process, the aramid and nylon fibers are repeatedly twisted and wound, followed by impregnation with three different impregnation solutions. This process significantly enhances the inter-fiber cohesion, thereby achieving a significant improvement in the overall strength of the material at the macroscopic level. This reinforcement mechanism not only optimizes the material's mechanical properties, such as tensile strength, abrasion resistance, and fatigue resistance, but also enables the final product to maintain high strength while achieving a significant weight reduction, meeting the lightweight requirements of aircraft tires; simultaneously, it further reduces energy consumption and costs during production and use.

[0023] More importantly, the composite skeleton material of this invention has higher strength, providing a more robust support structure for the tire. This effectively resists the enormous centrifugal force and ground friction generated during high-speed flight, significantly improving tire durability and service life. Simultaneously, the enhanced safety performance provides crucial protection for aviation safety, reducing potential risks caused by tire failure and improving overall flight safety. Detailed Implementation

[0024] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0025] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back, etc.), the directional indications are only used to explain the relative positional relationship and movement of the components in a specific posture. If the specific posture changes, the directional indications will also change accordingly.

[0026] Furthermore, if the embodiments of this invention involve descriptions such as "first" or "second," these descriptions are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined with "first" or "second" may explicitly or implicitly include at least one of those features. Additionally, if the word "and / or" appears throughout the text, it means including three parallel solutions; for example, "A and / or B" includes solution A, solution B, or a solution that simultaneously satisfies A and B. Furthermore, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or impossible to implement, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed by this invention.

[0027] This invention provides a method for preparing aramid and nylon skeleton materials for aircraft tire crown strips, comprising the following steps:

[0028] S1. Initial twisting: On a ring twisting machine, a 1100 dtex aramid filament is twisted in the Z direction with a twist of 240-300 twists / meter, for a total of three twists; On a ring twisting machine, a 940 dtex nylon filament is twisted in the Z direction with a twist of 160-200 twists / meter, for a total of two twists.

[0029] S2. Plying and twisting: Ply the three aramid yarn strands and two nylon yarn strands together, and twist the plied yarn in the opposite S direction with a twist of 240-300 twists / meter to obtain a blended yarn (i.e., 1100dtex x 3 + 940dtex x 2).

[0030] S3. Impregnation: The blended yarn is immersed in a first-bath impregnation solution at a temperature of 25-30°C for 2-6 seconds. The first-bath impregnation solution is an aqueous adhesive. The yarn is then removed and dried at 100-120°C for 1.2-1.5 minutes. The dried yarn is then immersed in a second-bath impregnation solution at a temperature of 25-30°C. The second-bath impregnation solution is a CBI-50 aqueous solution. The yarn is then removed and activated at 180-215°C for 1.2-1.5 minutes. After activation, the yarn is immersed in a third-bath impregnation solution at a temperature of 20-30°C for 2-6 seconds. The third-bath impregnation solution is an RFL adhesive. Finally, the yarn is removed and heat-set at 210-235°C for 1.2-1.5 minutes.

[0031] S4. To prepare the finished cord, the heat-set blended cord is placed in a drawing machine and drawn at 210-235℃. The drawing tension of the drawing machine is 280-320g / cord, and the machine speed is 4-6 meters / minute, thus obtaining the finished cord.

[0032] Furthermore, the ratio of the length of the aramid filament to the length of the nylon filament is 1.08:1.

[0033] Furthermore, the preparation method of the one-bath impregnation solution is as follows: at a temperature of 20-25°C, first add 0.1g of wetting agent OT with a solid content of 10%-15% to 96g of softened water and stir evenly, then add 2.9g of EX-313 epoxy resin (where EX-313 refers to the model of water-based epoxy resin), stir evenly, and after standing for eight hours, the one-bath impregnation solution is obtained.

[0034] Furthermore, the preparation method of the two-bath impregnation solution is as follows: at a temperature of 20-25°C, 10g of CBI-50 (CBI-50 is a blocked isocyanate) with a solid content of 50% is poured into 90g of softened water and stirred evenly to obtain the two-bath impregnation solution.

[0035] Furthermore, the preparation method of the three-bath impregnation solution includes the following steps:

[0036] 1) At room temperature of 20-25℃, add 2Kg of resorcinol-formaldehyde resin with a solid content of 75% to 23Kg of softened water and stir evenly. Then slowly add 3Kg of ammonia water with a concentration of 25% while stirring until all of it is added. Stir evenly and let stand for 8 hours to obtain solution A.

[0037] 2) At room temperature of 20-25℃, 35Kg of butyl rubber latex with a solid content of 40% was mixed with 15Kg of softened water and 5KG of natural rubber latex with a solid content of 60%, and stirred evenly to obtain solution B.

[0038] 3) At room temperature of 20-25℃, 1 kg of formaldehyde is mixed with 11 kg of softened water to obtain solution C;

[0039] 4) At room temperature of 20-25℃, add solution A to solution B and stir well. Then slowly add solution C last, stirring constantly until all the solution is added and stirred well. After standing for 24 hours, the RFL adhesive is obtained.

[0040] This invention represents a significant technological breakthrough in the field of aircraft tire manufacturing. By introducing an innovative three-groove impregnation RFL process, it greatly enhances the adhesive strength between the cords and the tire carcass. This design not only ensures the structural stability of the tire under extreme operating conditions (such as high speed, high temperature, and high pressure), but also effectively prevents delamination problems caused by insufficient adhesive strength, significantly improving the safety and service life of aircraft tires.

[0041] Meanwhile, this invention also innovates in material selection, specifically choosing low-linear-density nylon as the core material. This nylon material itself possesses excellent mechanical properties and chemical stability, and through advanced multi-strand twisting technology, the cohesion between fibers is further enhanced, resulting in a significant improvement in the overall strength of the rope. This reinforcement mechanism not only optimizes the tire's load-bearing capacity and fatigue resistance but also reduces costs by decreasing material usage, demonstrating good economic benefits.

[0042] More importantly, the implementation of this invention not only reduces costs but also comprehensively improves the physical and chemical performance indicators of the product. Compared with previous patented technologies, the aviation tires of this invention exhibit superior performance in terms of wear resistance, aging resistance, and tear strength, meeting the urgent needs of the modern aviation industry for high-performance, high-reliability tires.

[0043] Table 1 shows a performance comparison between this patent and existing patented products:

[0044]

[0045] The above description is merely an optional embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural transformations made using the contents of the present invention under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included within the patent protection scope of the present invention.

Claims

1. A method for preparing aramid and nylon skeleton materials for aircraft tire crown strips, characterized in that, Includes the following steps: S1. Initial twisting: On a ring twisting machine, a 1100 dtex aramid filament is twisted in the Z direction with a twist of 240-300 twists / meter, for a total of three twists; On a ring twisting machine, a 940 dtex nylon filament is twisted in the Z direction with a twist of 160-200 twists / meter, for a total of two twists. S2. Plying and twisting: Ply the three aramid yarn strands and two nylon yarn strands together, and twist the plied yarn in the opposite S direction with a twist of 240~300 twists / meter to obtain a blended yarn rope. S3. Impregnation: The blended yarn is immersed in a first-bath impregnation solution at a temperature of 25-30°C for 2-6 seconds. The first-bath impregnation solution is an aqueous adhesive. The blended yarn is then removed and dried at 100-120°C for 1.2-1.5 minutes. The dried blended yarn is then immersed in a second-bath impregnation solution at a temperature of 25-30°C. The second-bath impregnation solution is a CBI-50 aqueous solution. The blended yarn is then removed and subjected to an activation reaction at 180-215°C for 1.2-1.5 minutes. After activation, the blended yarn is immersed in a three-bath impregnation solution for 2-6 seconds. The temperature of the three-bath impregnation solution is 20-30℃, and the three-bath impregnation solution is RFL solution. Finally, the blended yarn is taken out and heat-set at 210-235℃ for 1.2-1.5 minutes. S4. To prepare the finished cord, the heat-set blended cord is placed in a drawing machine and drawn at 210~235℃. The drawing tension of the drawing machine is 280~320g / cord and the machine speed is 4~6m / min. The finished cord is then obtained. The ratio of the length of the aramid filament to the length of the nylon filament is 1.08:

1.

2. The method for preparing aramid and nylon skeleton materials for aircraft tire crown strips according to claim 1, characterized in that, The preparation method of the one-bath impregnation solution is as follows: at room temperature of 20~25℃, first add 0.1g of wetting agent OT with a solid content of 10%~15% to 96g of softened water and stir evenly, then add 2.9g of EX-313 epoxy resin, stir evenly and let stand for eight hours.

3. The method for preparing aramid and nylon skeleton materials for aircraft tire crown strips according to claim 1, characterized in that, The preparation method of the two-bath impregnation solution is as follows: at room temperature of 20~25℃, pour 10g of CBI-50 with a solid content of 50% into 90g of softened water, stir evenly, and it can be used directly.

4. The method for preparing aramid and nylon skeleton materials for aircraft tire crown strips according to claim 1, characterized in that, The preparation method of the three-bath impregnation solution includes the following steps: 1) At room temperature of 20~25℃, add 2Kg of resorcinol-formaldehyde resin with a solid content of 75% to 23Kg of softened water, stir evenly, then slowly add 3Kg of ammonia water with a concentration of 25% while stirring, until all is added and stirred evenly. After standing for 8 hours, solution A is obtained. 2) At room temperature of 20~25℃, 35Kg of butyl rubber latex with a solid content of 40% was mixed with 15Kg of softened water and 5KG of natural rubber latex with a solid content of 60%, and stirred evenly to obtain solution B. 3) At room temperature of 20~25℃, 1Kg of formaldehyde is mixed with 11Kg of softened water to obtain solution C; 4) At room temperature of 20~25℃, add solution A to solution B and stir well. Then slowly add solution C last, stirring while adding, until all the solution is added and stirred well. After standing for 24 hours, the RFL adhesive is obtained.

Citation Information

Patent Citations

  • Manufacturing method for aramid fiber / chinlon composite cord for aircraft tires

    CN103498231A

  • Water-based adhesive for gum dipping and method for preparing stiff cord by using water-based adhesive

    CN117513006A

  • An Excellent Fatigue Resistance Tire Cord using Nylon 6,6 or Nylon 6 and Aramid, and Radial Tires Produced by the Same

    KR1020180063925A